1995
DOI: 10.2307/3578930
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Behavioral Effects in Non-Human Primates after Exposure to Ultrawideband Electromagnetic Radiation in the Microwave Frequency Range

Abstract: The effect of acute exposure to ultrawideband (UWB) electromagnetic radiation on the Primate Equilibrium Platform (PEP) task, where the monkey's task is to manipulate a joystick control to compensate for the random perturbations in the pitch plane that are generated by a computer at unpredictable intervals, was examined. The duration of the UWB exposure was 2 min at a pulse repetition rate of 60 Hz (total of 7200 pulses). The bandwidth of the pulse was 100 MHz to 1.5 GHz (peak power between 250-500 MHz) with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…This appears to be true even for very high peak powers and ultra wide band fields [Sherry et al, 1995]. However, there is always the possibility that PFs can produce auditory cues [Lin, 1990], so appropriate masking noise and/or positive control procedures should be part of the experimental design.…”
Section: Impact Of Rf Field Characteristicsmentioning
confidence: 99%
“…This appears to be true even for very high peak powers and ultra wide band fields [Sherry et al, 1995]. However, there is always the possibility that PFs can produce auditory cues [Lin, 1990], so appropriate masking noise and/or positive control procedures should be part of the experimental design.…”
Section: Impact Of Rf Field Characteristicsmentioning
confidence: 99%
“…In a recent report, Jauchem et al (1997) indicated no significant differences in heart rate and arterial blood pressure between UWBRexposed (pulse repetition rate 1 kHz, pulse rise time 300 ps and E-field strength 21 kV m ~') and control rats. Sherry et al (1995) exposed six monkeys to UWBR for 2 min (pulse frequency 60 Hz, pulse duration 5-10 ns, a total of 7200 pulses, bandwidth 100 MHz to 1.5 GHz, peak E-field strength of 250kVm"', and a whole-body SAR calculated to be 0.5mWkg _1 ). Each monkey was exposed to UWBR twice, with an interval of 6 days between exposures.…”
Section: Discussionmentioning
confidence: 99%
“…There have been relatively few studies in the literature on the biological effects of UWB exposure; however, reports by Sherry et al [1995] and Jauchem et al [1998a,b] challenge the notions proposed by Albanese et al [1994]. These studies have found no biological effect of UWB exposure and have used bioassays as diverse as proto-oncogene c-fos in the brain, levels of aspartate transaminase, alanine transaminase, creatine kinase, and amylase in the blood, and 30 behavioral and physiological tests.…”
Section: Introductionmentioning
confidence: 99%